KONSERVASI SUBAK ANGGABAYA: SUATU MODEL KONSERVASI LANSKAP BALI - Naniek Kohdrata; Putu Edhi Sutrisna (Jurnal Lanskap Indonesia, 2011)
Subak is one of Balinese cultural products that hastangible and intangible aspects. It also relates to Balinese landscape, social and culture. The tangible and intangible forms of subak are paddy field landscape and local agriculture system, which are well known as one of Bali’s landscape images.The environment conservation often collides with spatial and economy needs. Environment degradation is found in most of places  in the world and in Bali subaks as well. Bali is loosing subaks, which mostly caused by its agricultural landscape function transformation.The Anggabaya Subak, which is located in Denpasar city, is one among other subaks that situated in urban context. This condition has caused agricultural landscape transformation much more significant thanother subaks in rural areas. The existence of Anggabaya Subak will be at  risk if the agricultural landscape cannot give more benefits, economically, to the local community.Anggabaya Subak conservation can be used as a holistic conservation model of landscape, social, and culture in Bali. The Anggabaya Subak conservation is carried out by enhancing the subak functions. The subak expands its functions from primarily managing the landscape for agricultural crops to managing the agricultural landscape for tourism. Three factors that support the function enhancement are the agricultural landscape potential, subak organization capacity, and support from the local government.A functioning agricultural landscape as a tourism object is expected to answer the pressure of changing agricultural landscape. The sustainable and dynamic subak are anticipated to be able to maintain the image of Bali sustainable landscape.